The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1590/s1678-77572006000400012
|View full text |Cite
|
Sign up to set email alerts
|

PCNA and p53 expression in oral leukoplakia with different degrees of keratinization

Abstract: Leukoplakias are oral lesions that may have many clinical and histological aspects and they are usually associated with malignancy when dysplastic alterations are shown. However, these transformations may occur in non-dysplastic lesions that show harmless clinical aspect. For this reason, the proposal was to study the p53 and PCNA immunohistochemical expression in non-dysplastic leukoplakias, trying to correlate the results only with the epithelial keratinization degree. For this, 24 leukoplakias degrees I, II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…However, overexpression of p53 mutant protein has been demonstrated in precancerous and cancerous lesions of the oral cavity (Lawall Mde and Crivelini, 2006). Our results were in line with these observations.…”
Section: Discussionsupporting
confidence: 92%
“…However, overexpression of p53 mutant protein has been demonstrated in precancerous and cancerous lesions of the oral cavity (Lawall Mde and Crivelini, 2006). Our results were in line with these observations.…”
Section: Discussionsupporting
confidence: 92%
“…During the immunohistochemical analysis of the AC cases, we observed that p53 protein expression occurred in both basal and suprabasal layer epithelial cells. Equal immunolocalization has been obtained by other authors in different cases of premalignant oral lesions 6 , 9 , 14 , 15 , 23 , although Argawal, et al 2 (1998) observed that the p53 protein was only expressed in the nucleus of basal layer epithelial cells in cases of oral leukoplasias. It is implied that p53 protein expression in keratinocytes, and not in differentiated cells, supports the potential role of p53 in preventing early carcinogenesis 31 .…”
Section: Discussionmentioning
confidence: 76%
“…[ 9 ] Increased PCNA expression has also been seen as tissues progressed from the normal epithelium to malignancy. [ 10 18 ]…”
Section: Discussionmentioning
confidence: 99%